A ética profissional dos assistentes sociais - os valores que a fundamentam - Silva, Therezinha Polesi da (1992)
The Social Service is an eminently ethic profession for dealing with the most acute human problems, going from surviving strategies of poor people, to the struggle of the workforce for its rights, to the very personal problems in the family and society. The concem with professional ethlcs has been present among the Brazilian social workers, even betere the legal regulation of this profession, in 1962. The first Professional Ethics Code for Social Workers was prepared in 1947, by the Social Worker Brazilian Association. The present study, which is being presented here as a Master's Degree dissertation, is an attempt to comprehend the social worker professional ethics in the Brazilian reality, especially in the city of São Paulo, where I have been studying and working on the subject for 20 years